Hearing Loss Increases Inhibitory Effects of Prefrontal Cortex Stimulation on Sound Evoked Activity in Medial Geniculate Nucleus - De Vis, Chenae; Barry, Kristin M.; Mulders, Wilhelmina H. A. M. (Frontiers in Synaptic Neuroscience, 2022)
Sensory gating is the process whereby irrelevant sensory stimuli are inhibited on their way to higher cortical areas, allowing for focus on salient information. Sensory gating circuitry includes the thalamus as well as several cortical regions including the prefrontal cortex (PFC). Defective sensory gating has been implicated in a range of neurological disorders, including tinnitus, a phantom auditory perception strongly associated with cochlear trauma. Recently, we have shown in rats that functional connectivity between PFC and auditory thalamus, i.e. the medial geniculate nucleus (MGN), changes following cochlear trauma, showing an increased inhibitory effect from PFC activation on the spontaneous firing rate of MGN neurons. In this study, we further investigated this phenomenon using a guinea pig model, in order to demonstrate the validity of our finding beyond a single species and extend data to include data on sound evoked responses. Effects of PFC electrical stimulation on spontaneous and sound-evoked activity of single neurons in MGN were recorded in anaesthetized guinea pigs with normal hearing or hearing loss 2 weeks after acoustic trauma. No effect, inhibition and excitation were observed following PFC stimulation. The proportions of these effects were not different in animals with normal hearing and hearing loss but the magnitude of effect was. Indeed, hearing loss significantly increased the magnitude of inhibition for sound evoked responses, but not for spontaneous activity. The findings support previous observations that PFC can modulate MGN activity and that functional changes occur within this pathway after cochlear trauma. These data suggest hearing loss can alter sensory gating which may be a contributing factor towards tinnitus development.